Let’s Talk about Books: Strategies used by Female Booktubers to Engage Audiences - Sánchez-Rebato Valiente, Clara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This article studies the verbal communicative strategies of engagement of female booktubers from Spain, the United Kingdom and the United States. As starting point it reviews the online community of Booktube using the theoretical framework of the participatory culture. Methodologically, a multimodal discourse analysis was conducted but only contemplating the verbal aspects, supported by social semiotics. Results have highlighted how booktubers talk colloquially with their audience, including them in their discourse, taking care of them while encouraging possibilities of interaction or boosting forms of collaborating with third parties to benefit their audiences without any personal gain.